Juglans regia L. (Walnut) Leaf Extract Ameliorates Pulmonary Edema Against Airway Inflammation via Upregulation of Tight Junction Proteins and Heme Oxygenase-1 in the Lungs of Asthmatic Mice - Neelam Arshed; Arham Shabbir; Humaira Majeed Khan; Tabinda Fatima; Esraa M. Haji; Farhan K. Alswailmi; Ali F. Almutairy; Ashfaq Ahmad (Journal of Tropical Medicine)
Conclusion: Juglans regia L.’s hydroalcoholic extract possesses antiasthmatic activity by normalizing the TLC cells and DLC cells. Juglans regia L.’s hydroalcoholic extract resulted in the amelioration of pulmonary edema which is attributed to the upregulation of HO-1, occludin, and ZO-1 in the lung tissues of the Juglans regia L. treated groups when compared to the diseased control group. Administration of Juglans regia L.’s extract also reduces the scores of inflammation and vascular congestion by evaluation of the lungs’ histopathology in the disease control group when compared to the NC group.